Enhanced immunogenicity of the Brucella A19 ΔbtpB mutant leads to accelerated clearance in the host - Yuan, Ye; Bu, Xuan; Zhai, Yunyi; WuDong, Gaowa; Lu, Qing; Tang, Ting; Zhou, Dong; Liu, Wei; Jin, Yaping; Wang, Aihua (Frontiers in Immunology, 2026)
IntroductionBrucella is a Gram-negative facultative intracellular bacterium that can cause fever, abortion, and other symptoms in humans and various mammals. btpB, a type IV secretion system (T4SS) effector of Brucella, plays a critical role in regulating Brucella infection and inhibiting the host's innate immune response.MethodsIn this study, a btpB mutant strain of Brucella A19 (ΔbtpB) was constructed using homologous recombination, and its biological characteristics, virulence, and immunogenicity were systematically investigated.ResultsThe results showed that ΔbtpB exhibited weakened resistance to in vitro stress, while its growth characteristics did not differ significantly from the wild-type strain A19. In the mouse immunization model, ΔbtpB induced weaker splenic pathological damage, and the splenic bacterial load was significantly lower than that of A19, indicating its reduced virulence. Additionally, ΔbtpB infection elicited stronger humoral and cellular immune responses in mice, including higher antibody levels, increased levels of Th1 cytokines (such as IFN-γ and IL-2), and enhanced proliferation and activity of CD8+ cells. Detection of Th1 and Th2 cells revealed that ΔbtpB induced stronger Th1 and Th2 responses in the spleen in the early stage, but the Th2 response weakened in the middle and late stages of infection. Notably, ΔbtpB infection did not suppress natural killer (NK) cell activity and even significantly enhanced its cytotoxic activity compared to the A19 strain.ConclusionOur research demonstrates that ΔbtpB leads to a reduced survival capacity of Brucella, while enhancing its immunogenicity. This suggests btpB is an important target for the prevention of Brucella.